Оперативная оценка ресурсов углеводородов в пределах поисковых площадей и отдельных структур на шельфе методом частотно-резонансной обработки и интерпретации данных ДЗЗ - Левашов, С.П.; Якимчук, Н.А.; Корчагин, И.Н.; Божежа, Д.Н. (Геоінформатика, 2015)
Анализируются результаты применения метода частотно-резонансной обработки данных дистанционного зондирования Земли (ДЗЗ) для оперативной оценки перспектив нефтегазоносности отдельных структур на шельфе в районе пробуренных и проектных скважин. С использованием этой мобильной и оперативной технологии обработаны спутниковые снимки крупных поисковых участков и блоков на шельфах Карского, Черного и Азовского морей, южном шельфе ЮАР и юго-восточном шельфе Фолклендских островов. На площади обследования в Карском море в пределах одной структуры обнаружено 6 аномальных зон типа “залежь углеводородов (УВ)”, на локальном участке Туапсинского прогиба в Черном море – 5 аномальных зон; их существенно меньше, чем выявленных геофизическими исследованиями структур. Исследованиями в Азовском море в районе пробуренной скважины Белосарайская-1 (1400 м) показана возможность обнаружения залежей УВ в нарушенной части фундамента. В районе газового месторождения на шельфе ЮАР обнаружено и закартировано 13 аномальных зон типа “Gas”, многие из которых являются локальными участками для детального изучения и разбуривания. Это, практически, зоны “Sweet spots” в плотных песчаниках. Оценки пластового давления в 21 МПа в районе скважины Darwin на шельфе Фолклендских островов указывают на малую вероятность получения коммерческих притоков УВ из интервала глубин 4633–4681 м. Обнаруженные аномальные зоны представляют собой, по сути, проекции на земную поверхность контуров скоплений УВ в разрезе. Эта информация может использоваться для приближенной оценки ресурсов УВ в пределах обследованных участков и структур. Начало освоения обследованных лицензионных блоков с обнаруженных аномальных зон позволит, в целом, существенно ускорить и оптимизировать поисковый процесс. Мобильная технология частотно-резонансной обработки и декодирования данных ДЗЗ может использоваться для оперативной оценки перспектив нефтегазоносности отдельных структур и поисковых площадей в морских и океанических акваториях, включая труднодоступные Арктический и Антарктический регионы. Проаналізовано результати застосування методу частотно-резонансної обробки даних ДЗЗ для оперативної оцінки перспектив нафтогазоносності окремих структур на шельфі в районі пробурених та проектних свердловин. З використанням цієї мобільної та оперативної технології оброблено супутникові знімки великих пошукових ділянок і блоків на шельфах Карського, Чорного та Азовського морів, південному шельфі ПАР та південно-східному шельфі Фолклендських островів. На площі обстеження в Карському морі в межах однієї структури виявлено 6 аномальних зони типу “поклад вуглеводнів (ВВ)”, на локальній ділянці Туапсинського прогину в Чорному морі – 5 аномальних зон; їх істотно менше, ніж виявлених геофізичними дослідженнями структур. Дослідженнями в Азовському морі в районі пробуреної свердловини Білосарайська-1 (1400 м) показано можливість виявлення покладів ВВ у порушеній частині фундаменту. В районі газового родовища на шельфі ПАР виявлено та закартовано 13 аномальних зон типу “Gas”, багато з яких є локальними ділянками для детального вивчення та розбурювання. Це, практично, зони “Sweet spots” у щільних пісковиках. Оцінки пластового тиску в 21 МПа в районі свердловини Darwin на шельфі Фолклендських островів вказують на малу ймовірність отримання комерційних припливів ВВ з інтервалу глибин 4633–4681 м. Виявлені аномальні зони є, по суті, проекціями на земну поверхню контурів скупчень ВВ у розрізі. Цю інформацію можна використовувати для наближеної оцінки ресурсів ВВ у межах обстежених ділянок і структур. Початок освоєння обстежених ліцензійних блоків з виявлених аномальних зон дасть змогу, в цілому, істотно прискорити та оптимізувати пошуковий процес. Мобільну технологію частотно-резонансної обробки та декодування даних ДЗЗ можна використовувати для оперативної оцінки перспектив нафтогазоносності окремих структур і пошукових площ у морських та океанічних акваторіях, включаючи важкодоступні Арктичний і Антарктичний регіони. Purpose. The purpose of the paper is to study the possibility of a mobile method of remote sensing data frequency-resonance processing used for operative assessment of the petroleum potential of individual structures and objects in the area of drilled and projected wells within offshore. To conduct experimental studies on the shelf of the Kara, Black and Azov seas, on the southern shelf of the South African Republic and south-eastern shelf of the Falkland Islands.
Design/methodology/approach. Experiments were carried out with using the mobile technology of frequency-resonance processing, and interpretation of remote sensing data, which is the direct method of oil and gas exploration and operates within the “substantial” paradigm of geophysical investigations. The technologies and methods developed on the principles of this paradigm are aimed at searching a particular (desired in each case) substance – oil, gas, condensate, gold, zinc, uranium, etc.
Findings. Four anomalous zones of the “oil + gas + condensate” type and two anomalous zones of the “oil + gas” type were discovered and mapped within the surveyed area in the Kara Sea. The estimates of maximum values of fluid pressures in reservoir vary from 19,1 to 29,4 MPa within the detected anomalies. The total area of all the anomalies equals 510 km2; with regard to the surveyed area this is 12,29 %. Within the local area in Tuapse Trough in the Black Sea four anomalies of the “gas” type and one anomaly of the “gas + condensate” type were revealed. There are anomalous zones significantly small than the structures identified by geophysical research.
The results of the studies in the Azov Sea showed that the well “Belosarayskaya-1” (1400 m depth) drilled within the structure of the same name does not explicitly resolve the question about the prospects of commercial hydrocarbons accumulations found within it, as it opened only the sediments of the cross-section. Vertical scanning of the cross-section near the well confirmed the possibility of hydrocarbon deposits detection in the fractured part of the basement. Within the tested block in the area of the F-O gas field on the South Africa offshore, 13 anomalous zones of the “gas” type of varying size and intensity were discovered and mapped. Parameters of many anomalous zones (areas and maximum estimates of fluid pressure in the reservoirs) allow us to classify them as promising objects the probability of industrial (commercial) gas inflows from which is relatively high. The observed anomalies should be considered as priority local areas for detailed study with geophysical methods and drilling. In fact, they can be considered as “Sweet spots” zones in tight sandstones. Based on the results of remote sensing data processing in the area of the Darwin well drilled in the Falkland Islands offshore, the maximum values of reservoir pressure were estimated at 21 MPa. At the resonance frequencies of gas at higher pressures anomalous effects did not appear. This means that from the established Darwin well collector at the depths of 4633–4681 m the likelihood of commercial hydrocarbons inflows is very low.
Practical value/implications. Discovered anomalous zones are, in fact, the projections into surface of hydrocarbon accumulations contours in the cross-section. This additional information can be used for the approximate assessments of hydrocarbon resources within the surveyed areas and structures. The development of the surveyed license blocks starting from detected anomalous zones will generally make it possible to significantly accelerate and optimize the prospecting process. Mobile technology of frequency-resonance processing and interpretation (decoding) of remote sensing data can be used for operative assessment of the petroleum potential of individual structures and prospecting areas in marine and ocean waters, the difficult to access and remote Arctic and Antarctic regions included.